The determinants and the moderating effects of compensation on fast food restaurant employees job performance - Muhamad Saufiyudin, Omar (2021)
Every organisation including the food and beverage businesses needs an outstanding employee to attain the organisational success. One essential factor that determines organisational success is the employee’s job performance. Employee’s job performance has become a critical issue across the globe, due to its significance in maintaining an organisation’s success. Nevertheless, within the context of fast food restaurants, there has been limited studies investigating the influence between employee job attitude, motivation, job involvement on job performance. In addition, studies pertaining to employee’s compensation as a moderator are also limited. In addition, studies that investigated the difference between local and foreign employees’ job performance are scarce. Therefore, this study aims to examine the influence between employee’s job attitude, motivation and job involvement, on job performance; to investigate the moderating effect of employee compensation on job performance; and to compare employee job attitudes, motivation and job involvement, on job performance between local and foreign employees. By adapting quantitative and survey method, the questionnaires were distributed to non-managerial employees at four selected fast-food brand restaurants at the Federal Territory of Kuala Lumpur and Selangor, Malaysia. A total of 688 useable questionnaires were analysed. The multiple regression analysis revealed that employee’s job attitude, motivation, and job involvement significantly and positively influenced employee’s job performance. Therefore, to improve employee job performance, managers and organisations must enhance employee’s job attitude, motivation, and job involvement. While, the hierarchical multiple regressions analysis revealed that employee’s compensation moderated the relationships of employee’s job performance with employee’s job attitude, motivation and job involvement. Hence, enhancing employee’s compensation will positively affect employee’s job attitude, motivation and job involvement, and consequently improve employee’s job performance. In addition, the independent samples t-test showed differences in terms of job attitude, motivation, job involvement on job performance between local and foreign employees. Moreover, foreign employees’ job attitude, motivation, job involvement and job performance outperformed those of local employees. Hence, managers and organisations should strategize to increase their effort in order to improve local employees’ job performance. This empirical study contributes to the literature on fast-food businesses to enhance employees’ job performance in the context of Malaysia.